The experiences of the Universidade Federal de Santa Catarina's Library Working Group on COVID-19 Prevention. (March 2022) - Righetto, Guilherme Goulart; Rossi, Tatiana; Soares, Juliane Fonseca
This article presents a brief overview of the consequences of the COVID-19 pandemic in the context of Brazilian university libraries, as well as the efforts made by those institutions. It aims to report the experiences of the University Library Working Group at the Universidade Federal de Santa Catarina, located in southern Brazil, in COVID-19 prevention. It describes the guidelines that the Working Group established and the perspectives for returning to face-to-face work. It considers the relevance of the role of libraries in accessing and disseminating science information. It highlights the opportunities for change and advances in study, research and services aimed at libraries in general. The article concludes that the University Library at the Universidade Federal de Santa Catarina, through the Working Group fulfilling its role of supporting teaching, made it possible to articulate an information exchange network about COVID-19 with public servants, where the Working Group has carried out research and guided the management of the University Library in conducting the provision of face-to-face and remote services securely, both for users and the BU/UFSC staff (or employees).